Cryopreservation of Hepatocyte Microbeads for Clinical Transplantation - Jitraruch, Suttiruk (Cell Transplant, 2017)
Intraperitoneal transplantation of hepatocyte microbeads is an attractive option for the management of acute liver failure. Encapsulation of hepatocytes in alginate microbeads supports their function and prevents immune attack of the cells. Establishment of banked cryopreserved hepatocyte microbeads is important for emergency use. The aim of this study was to develop an optimized protocol for cryopreservation of hepatocyte microbeads for clinical transplantation using modified freezing solutions. Four freezing solutions with potential for clinical application were investigated. Human and rat hepatocytes cryopreserved with University of Wisconsin (UW)/10% dimethyl sulfoxide (DMSO)/5% (300 mM) glucose and CryoStor CS10 showed better postthawing cell viability, attachment, and hepatocyte functions than with histidine–tryptophan–ketoglutarate/10% DMSO/5% glucose and Bambanker. The 2 freezing solutions that gave better results were studied with human and rat hepatocytes microbeads. Similar effects on cryopreserved microbead morphology (external and ultrastructural), viability, and hepatocyte-functions post thawing were observed over 7 d in culture. UW/DMSO/glucose, as a basal freezing medium, was used to investigate the additional effects of cytoprotectants: a pan-caspase inhibitor (benzyloxycarbonyl-Val-Ala-dl-Asp-fluoromethylketone [ZVAD]), an antioxidant (desferoxamine [DFO]), and a buffering and mechanical protectant (human serum albumin [HSA]) on RMBs. ZVAD (60 µM) had a beneficial effect on cell viability that was greater than with DFO (1 mM), HSA (2%), and basal freezing medium alone. Improvements in the ultrastructure of encapsulated hepatocytes and a lower degree of cell apoptosis were observed with all 3 cytoprotectants, with ZVAD tending to provide the greatest effect. Cytochrome P450 activity was significantly higher in the 3 cytoprotectant groups than with fresh microbeads. In conclusion, developing an optimized cryopreservation protocol by adding cytoprotectants such as ZVAD could improve the outcome of cryopreserved hepatocyte microbeads for future clinical use.